Usaha Street Food Pedagang Kaki Lima di Jalan Udayana Rembiga Mataram Nusa Tenggara Barat - Putu Ayu Pratiwi Duta Siwantari; I Putu Gede; I Gede Angga Permana (Jurnal Pengabdian Dosen Republik Indonesia, 2026)
The community service program titled “Street Food Business of Street Vendors at Udayana Street, Rembiga, Mataram, West Nusa Tenggara” aimed to enhance the capacity, hygiene, and competitiveness of local street food vendors through training in business management, digital marketing, and good food sanitation practices. The program included stages of planning, preparation of tools and materials, training, and mentoring, all of which were successfully implemented according to the agreed schedule and enthusiastically followed by the participants. Evaluation results indicated a significant improvement in participants’ business management skills. Approximately 80% of the vendors were able to use simple bookkeeping systems and separate personal and business finances. In terms of digitalization, 72% of vendors began utilizing social media platforms such as Instagram and Facebook for promotion, leading to a 10–30% increase in daily orders within two months after the training. Regarding hygiene, all participants applied Good Hygiene Practices (GHP), and 90% of food stalls improved in cleanliness, layout, and the use of hygienic serving tools. The addition of visual branding elements such as logos, banners, and menus also enhanced the overall image of the Udayana Street food area as a culinary destination in Mataram City. Overall, this program has made a tangible contribution to strengthening the local economy by improving business management capacity, adopting digital technology, and implementing higher hygiene standards. The program’s success was supported by collaboration among universities, local government, and the street vendors’ community, creating a sustainable empowerment ecosystem.